Rising CO2 can alter fodder–weed interactions and suppression of Parthenium hysterophorus. (12th November 2014) - Khan, N; George, D; Shabbir, A; Hanif, Z; Adkins, S W; Swanton, Clarence
Summary Three C4 grass (Setaria incrassata, Astrebla squarrosa and Bothriochloa decipiens) and one C3 legume (Clitoria ternatea) suppressive fodder species, were re‐evaluated against the growth of the C3Parthenium hysterophorus under an ambient (390 μmol mol−1) and an elevated atmospheric CO2 concentration (550 μmol mol−1). Under the elevated atmospheric CO2, shoot dry biomass and suppression index (SI) value of the C4S. incrassata were both reduced by 32% and 0.7 respectively, while those for A. squarrosa were reduced by 23% and 0.3. In contrast and under the same elevated atmospheric CO2 concentration, the shoot dry biomass and SI of the C4B. decipiens were increased by 8% and 0.1 respectively, while those for the C3C. ternatea were increased by 38% and 0.8. Our results suggest that C3 fodder plants along with certain C4 species could be utilised for the effective management of P. hysterophorus under the future elevated atmospheric CO2 conditions. However, this system needs more fodder species to be investigated. Our results suggest that rising CO2per se may alter the efficacy of suppressive fodder management of an invasive C3 species, P. hysterophorus.